Pengaruh Belanja Pegawai, Barang, Jasa, dan Modal terhadap Efisiensi Anggaran Pemerintah Daerah - Nadila Atqia Khairiyah; Vivi Oktari (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research investigates the impact of employee expenditure, goods and services expenditure, and capital expenditure on budget efficiency in the Ministry of Religious Affairs of Tasikmalaya Regency. Employing quantitative associative methodology with multiple linear regression analysis on time series data from 2022-2024, the study employs Principal Component Analysis to resolve multicollinearity issues between goods and services and capital expenditure. Findings reveal that capital expenditure demonstrates the most significant positive influence on budget efficiency (β = 10.036; p = 0.000), followed by goods and services expenditure (β = 1.353; p = 0.000), while employee expenditure shows insignificant impact (p = 0.329). The Adjusted R Square of 0.997 indicates that these three expenditure components explain 99.7% of budget efficiency variation. The research proposes an expenditure structure-based efficiency approach, integrating the simultaneous relationship between expenditure types and filling the gap in existing literature that primarily examines components separately. Practical recommendations include restructuring budget allocation to reduce employee expenditure proportions, implementing performance-based budgeting, prioritizing capital investment, and strengthening monitoring systems for optimal fiscal management.